The Survival of Family Firms: The Importance of Control and Family Ties - Francesca Lotti; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
The aim of this paper is to analyze the survival patterns of a group of family firms which have already spent at least twenty-five years in the market. To this end, we use the Kaplan-Meier product limit estimator supplemented with qualitative information gathered by direct observation and discussions with entrepreneurs. The main findings of the paper are that small family firms which have reached their thirtieth year in the market face a very high risk of sudden exit, increasing with firm age. Further control carried out by means of interviews with entrepreneurs identifies problems connected with succession as one of the main causes of the decision to close down.
Keywords: 330